2021
DOI: 10.33774/chemrxiv-2021-n8lt5
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chemically Fueled Self-sorted Hydrogels

Abstract: Narcissistic self-sorting in supramolecular assemblies can help to construct materials with more complex hierarchies. Whereas controlled changes in pH or temperature have been used to this extent for two-component self-sorted gels, here we show that a chemically fueled approach can provide three-component materials with high precision. The latter materials have interesting mechanical properties, such as enhanced or suppressed stiffness, and intricate multi-step gelation kinetics. In addition, we show that we c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…As such, at higher GdL concentrations the authors observed a fast gel-sol-gel conversion whereas at lower GdL concentrations, the solution state was maintained for much longer. In more recent work 99 , the authors looked at three chemically similar gelators, and showed that self-assembly into fibers can shield monomers from deactivation (by dithionite).…”
Section: Recently Singh Et Al Developed a New Reaction Cyclementioning
confidence: 99%
“…As such, at higher GdL concentrations the authors observed a fast gel-sol-gel conversion whereas at lower GdL concentrations, the solution state was maintained for much longer. In more recent work 99 , the authors looked at three chemically similar gelators, and showed that self-assembly into fibers can shield monomers from deactivation (by dithionite).…”
Section: Recently Singh Et Al Developed a New Reaction Cyclementioning
confidence: 99%